Chimeric virus-like particles of prawn nodavirus displaying hepatitis B virus immunodominant region: biophysical properties and cytokine response - Ninyio, Nathaniel Nyakaat; Ho, Kok Lian; Yong, Chean Yeah; Chee, Hui Yee; Hamid, Muhajir; Ong, Hui Kian; Abdul Razak, Mariatulqabtiah; Tan, Wen Siang (Multidisciplinary Digital Publishing Institute, 2021)
Hepatitis B is a major global health challenge. In the absence of an effective treatment for the disease, hepatitis B vaccines provide protection against the viral infection. However, some individuals do not have positive immune responses after being vaccinated with the hepatitis B vaccines available in the market. Thus, it is important to develop a more protective vaccine. Previously, we showed that hepatitis B virus (HBV) ‘a’ determinant (aD) displayed on the prawn nodavirus capsid (Nc) and expressed in Spodoptera frugiperda (Sf9) cells (namely, Nc-aD-Sf9) self-assembled into virus-like particles (VLPs). Immunisation of BALB/c mice with the Nc-aD-Sf9 VLPs showed significant induction of humoral, cellular and memory B-cell immunity. In the present study, the biophysical properties of the Nc-aD-Sf9 VLPs were studied using dynamic light scattering (DLS) and circular dichroism (CD) spectroscopy. Enzyme-linked immunosorbent assay (ELISA) was used to determine the antigenicity of the Nc-aD-Sf9 VLPs, and multiplex ELISA was employed to quantify the cytokine response induced by the VLPs administered intramuscularly into BALB/c mice (n = 8). CD spectroscopy of Nc-aD-Sf9 VLPs showed that the secondary structure of the VLPs predominantly consisted of beta (β)-sheets (44.8%), and they were thermally stable up to ~52 °C. ELISA revealed that the aD epitope of the VLPs was significantly antigenic to anti-HBV surface antigen (HBsAg) antibodies. In addition, multiplex ELISA of serum samples from the vaccinated mice showed a significant induction (p < 0.001) of IFN-γ, IL-4, IL-5, IL-6, IL-10, and IL-12p70. This cytokine profile is indicative of natural killer cell, macrophage, dendritic cell and cytotoxic T-lymphocyte activities, which suggests a prophylactic innate and adaptive cellular immune response mediated by Nc-aD-Sf9 VLPs. Interestingly, Nc-aD-Sf9 induced a more robust release of the aforementioned cytokines than that of Nc-aD VLPs produced in Escherichia coli and a commercially used hepatitis B vaccine. Overall, Nc-aD-Sf9 VLPs are thermally stable and significantly antigenic, demonstrating their potential as an HBV vaccine candidate.